2004
DOI: 10.1007/s00280-004-0811-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the proteasome inhibitor bortezomib alone and in combination with chemotherapy in the A549 non-small-cell lung cancer cell line

Abstract: Bortezomib improves efficacy in combination with gemcitabine and carboplatin in NSCLC, but sequential effects are important and must be considered when developing therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 47 publications
3
80
0
Order By: Relevance
“…12,27 Others found sequential effects with regard to the time of administration using gemcitabine and carboplatin in combination with bortezomib. 14 We chose docetaxel and bortezomib as these two agents have shown to improve survival and life quality of patients with NSCLC as single agents in the second-line therapy. In contrast to p53 gene transfer, no synergism was found for the combination between bortezomib and the cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,27 Others found sequential effects with regard to the time of administration using gemcitabine and carboplatin in combination with bortezomib. 14 We chose docetaxel and bortezomib as these two agents have shown to improve survival and life quality of patients with NSCLC as single agents in the second-line therapy. In contrast to p53 gene transfer, no synergism was found for the combination between bortezomib and the cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…12 The proteasome degrades the tumor suppressor p53, which is required for the transcription of a number of genes involved in cell-cycle control and DNA synthesis. 13 Wild-type p53 is stabilized by proteasome inhibition in cancer cell lines, 14,15 suggesting a mechanism of bortezomib-induced apoptosis that may be relevant in suppressing cancer progression. 16,17 We focussed on bortezomib as a promising agent to investigate if its combination with p53 gene transfer might enhance cytotoxicity in NSCLC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…17,27,28 The administration of gemcitabine in combination with bortezomib resulted in sensitization, or even enhancement, of the effect of gemcitabine in preclinical models. 17,[29][30][31][32] Moreover, proteasome inhibitors may overcome tumor resistance to gemcitabine by reducing NF-kB activity, 17,28 down-regulation of Bcl-2, 15,17 and stabilization of the cyclin kinase inhibitors p21 and p27. 15 A Phase I clinical trial to determine the dose-limiting toxicities (DLTs) and maximum tolerated dose (MTD) of bortezomib in combination with gemcitabine in patients with incurable advanced solid tumors was conducted.…”
Section: Methods Bortezomib Was Administered As An Intravenous Bolusmentioning
confidence: 99%
“…Novel drugs that aim at specific intracellular pathways related to the distinctive properties of cancer cells continue to be developed. It has been reported that proteasome inhibitor bortezomib (ps-341, Velcade) inhibits lung cancer cells (16,17). However, the role of Mg132 in lung cancer cells is not fully understood.…”
Section: Introductionmentioning
confidence: 99%